EFFECT OF CONTACT TIME ON THE ACUTE TOXICITY OF MERCURY TO SCAlE CARP - Das, Shyamal Chandra Sukla; Datta, Subhendu (Journal of Indian Fisheries Association, 2008)
The behaviour of metals in aquatic ecosystems is dependent on various environmental factors. Experiments were conducted in five different contact times (0.5, 2, 12, 24 and 48h) between soil sediment and mercury on Cyprinus carpio var communis. It was observed that contact time with soil sediment had significant effect in reducing the toxicity of mercury. Higher the time of contact, greater the effect. Medium hard water (150 mg/l CaC03 of total hardness) had the highest effectas compared to other water in reducing the toxicity of mercury when combined with underlying soil sediment. With the increase in contact time, complexation and adsorption of inorganic mercury ions with the dissolved and particulate phases of water and soil sediment were increased; thereby bioaccumulation of mercury ions by scale carp was more. Applicability of the result of this experiment in natural ecosystems was also suggested.Keywords: Mercury, Cyprinus carpio var communis, contact time, acute toxicity.